PROFIL JURUSAN PENDIDIKAN LUAR BIASA SEBAGAI ORGANISASI YANG BELAJAR - Tarjiah, Indina (Perspektif Ilmu Pendidikan, 2017)
The Departement of The Special Education is a unit in The School of Education, State University of Jakarta which has to be developed to meet its objectives and to serve the need of society. This study conducted a survey to know how this Department as an organization to develop itself by practicing the learning organization theory. The study found out that although The Department is making some changes to improve its quality, a further study is needed to get more data and to enrich the findings to ensure that this Department has been practiced learning organization principles.